Reconciling Indigenous Practices and Islamic Principles: A Comparative Analysis of the Fiqh Principles ‘Al-Dararu Yuzal’ and ‘Al-Adah Muhakkamah’ in the Panai Cultural Practice of Bugis Weddings - Amalia, Ainun (Faculty of Islam Nusantara, Nahdlatul Ulama University of Indonesia (Unusia) Jakarta., 2025)
This study aims to analyze the application of fiqh principles in the “Panai” tradition within Bugis marriage customs. Panai refers to a monetary payment that a male suitor is required to provide to the bride's family to cover wedding expenses. In the Bugis tradition, Panai is considered an essential component of the dowry, functioning almost as a precondition. Without Panai, marriages within this culture are unlikely to proceed. Over time, the meaning and significance of Panai have evolved, influenced by various social factors. It now serves as a measure of a woman's family’s social status, with its value increasing for women deemed beautiful, educated, or employed in prestigious professions such as civil service. The Bugis community upholds the culture of